Baby food industry interference with infant feeding international regulation—A case study on the standard for follow-up formula - Silva, Kimielle Cristina; Castro, Inês Rugani Ribeiro de; Carvalho, Camila Maranha Paes de; Camargo, Kenneth Rochel de (Frontiers in Public Health, 2022)
Introduction Globally, first-food systems have changed and breastfeeding has decreased due to the increased growth in commercial breast milk substitute (BMS) consumption, which includes both follow-up and toddler formulas. These products are manufactured by a small number of corporate leaders in international BMS sales. Discussions for global regulation of these products take place in the Codex Alimentarius and are permeated by the strong participation of these corporations in the Codex committees. Objective In the present study, the participation of the baby food industry in the review of the follow-up formula standard in the Codex Committee on Nutrition and Foods for Special Dietary Uses (CCNFSDU) was analyzed. Methods The analysis of the CCNFSDU documents was based on the period from 2009 to 2019 and used quantitative and qualitative approaches. Compositional and participation data from country delegations and observer organizations on the representative profiles of the involved institutions and the baby food industry's involvement in this process were established systematically. Results In total, 134 out of the 189 Codex Alimentarius member countries engaged in the standard review process, of which 28% were involved in the entire process. The private sector was present in 81% of the most assiduous member state delegations to the meetings. Furthermore, 60% of the observer organizations involved in the review process were business associations representing industry interests. Moreover, the International Special Dietary Foods Industries was the only business association with observer status in the CCNFSDU that was specifically dedicated to representing the baby food industryduring the review process. Conclusion These research results expand the body of evidence confirming the expressive and disproportionate participation of baby food industries and their representatives in the discussion processes within the scope of the CCNFSDU. However, studies investigating the Codex and the public documents of its respective committees are limited. Thus, this was the first study to analyze the influence of the baby food industry on BMS global regulatory compliance.